ANALYZING THE USES OF DIFFERENT BRAND MANAGEMENT STRATEGIES OF BANK: A STUDY ON PUBLIC BANK - Fakir, Shamim; Naeem, Abdullah Al; Karim, Syed Manzurul (American Finance & Banking Review, 2021)
Brand management strategies are a series of techniques used to increase the perceived value of a product or service. Brand management strategies are a series of techniques used to increase the perceived values of all products or services. The objective of the report is to analyze the uses of different brand management strategies of a public bank in Bangladesh. The paper is more important for marketers to know the significance of the uses of different brand management strategies of the public banks. This paper is most significant for the executives to gain a lot of customers by the use of brand management strategies. This is descriptive when the data is analyzed through a structured questionnaire and it is exploratory when the data is analyzed through in-depth interviews. This study is quantitative and qualitative in nature. The quantitative strategy will be utilized on account of the potential for speculation of discoveries. The targeted population of this study was the clients of public banking in Bangladesh. Data was collected using depth interview questionnaire and survey questionnaire. Data were analyzed quantitatively using SPSS, which was a statistical method for analyzing numerical data. The researcher distributed the questionnaires to 50 executives and employees of the public bank who has been asked through questionnaire and non-probability judgmental sampling was taken from an in-depth interviews w with the customers and also use the survey questionnaire to the 100 customers.JEL Classification Codes: M38.